The Effect of Work Motivation, Auditor Competence and Auditor Functional Position on Auditor Performance at Regency/ City Inspectorates in Riau Province - Defi Afriani; Nur Anita (AKUNTABILITAS, 2023)
This research attempts to ascertain how work motivation, auditor proficiency, and functional position affect auditor performance at the Regency/City Inspectorate in Riau Province. A quantitative technique is used in this study. There were 65 participants in this study, and purposive sampling was used in the sampling process. Multiple linear regression analysis approaches are used to process the data in the SPSS 25 application. The findings indicated that the auditor's functional position, auditor competency, and partial work motivation variables all had beneficial effects on auditor performance. The auditor's competency variable had no influence. The implication of this research is that the District/City Inspectorate in the Province of Riau can continue to improve its audit performance by performing or training that improves its audit ability so that auditors can perform their tasks to good government.